Thank You to Our 2019 Reviewers. Issue 8 (19th August 2020) - East, Amy E.; Finnegan, Noah Joseph; Hoitink, A. J. F. (Ton); Sergienko, Olga V.
Abstract: During 2019, the Journal of Geophysical Research‐Earth Surface handled a record‐high number of submitted manuscripts. Managing these in order to deliver the highest‐quality published science relies, of course, on obtaining quality peer review. We all recognize the demand that this places on the reviewers' time, especially as members of the Earth surface scientific community receive ever increasing numbers of requests to review manuscripts for many journals. The editors wish to extend our sincere thanks to all the 674 reviewers who volunteered their time to provide 962 reviews for JGR‐Earth Surface in 2019. We certainly appreciate the time and effort that these reviewers have put into writing insightful, constructive review comments, an essential part of moving the science forward. Key Point: The Editors thank the 2019 peer reviewers